2008
DOI: 10.1099/jmm.0.47736-0
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile TxAC314 and SLP-36kDa enhance the immune response toward a co-administered antigen

Abstract: This study evaluated the in vivo adjuvant activity of two peptides derived from Clostridium difficile: a fragment of the receptor-binding domain of toxin A (TxA C314 ) and a fragment of the 36 kDa surface-layer protein (SLP-36kDa) from strain C253. Their ability to affect the magnitude, distribution and polarization of the immune response against fibronectin-binding protein A (FnbpA), a protective vaccine antigen against Staphylococcus aureus, was evaluated using two different routes of immunization: intranasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…In our previous study 37 and consistent with others, 35,36 we indicated that the N-terminus of TcdB was able to elicit a protective antibody response. In contrast, the RBD of TcdA has potent adjuvant activity 40 , and has been used as vaccine candidates in several studies. 28,34,40 Therefore, we hypothesized that a fusion protein containing the N-terminus of TcdB and RBD of TcdA would be immunogenic and sufficient to induce protection against both toxins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study 37 and consistent with others, 35,36 we indicated that the N-terminus of TcdB was able to elicit a protective antibody response. In contrast, the RBD of TcdA has potent adjuvant activity 40 , and has been used as vaccine candidates in several studies. 28,34,40 Therefore, we hypothesized that a fusion protein containing the N-terminus of TcdB and RBD of TcdA would be immunogenic and sufficient to induce protection against both toxins.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the RBD of TcdA has potent adjuvant activity 40 , and has been used as vaccine candidates in several studies. 28,34,40 Therefore, we hypothesized that a fusion protein containing the N-terminus of TcdB and RBD of TcdA would be immunogenic and sufficient to induce protection against both toxins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future vaccines to reduce or prevent colonization with C. difficile As a C. difficile toxoid vaccine is unlikely to affect colonization, alternative vaccine candidates are being explored that may reduce or prevent this first step in the pathogenesis of CDI (Brun et al, 2008;Ní Eidhin et al, 2008;Péchiné et al, 2007). Péchiné et al (2005a, b) have evaluated C. difficile surface proteins, including the flagellar cap protein FliD and Cwp84, as vaccine antigens in a human flora-associated mouse model.…”
Section: Active Immunization With a C Difficile Toxoid Vaccine In Humentioning
confidence: 99%